KOLABORASI PENGABDIAN INTERNASIONAL: EDUKASI PENGARUSUTAMAAN GENDER DALAM PARTISIPASI POLITIK MELALUI PENDEKATAN THEORY OF PlANNED BEHAVIOR DI KAMPUNG TOK MENG NEGARA BAGIAN TERENGGANU MALAYSIA - Panca Setyo Prihatin; Normala Binti Riza; Satrio Abdillah; Dita Fisdian Adni (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2025)
This service activity aims to provide education regarding the use of the theory of planned behavior in mainstreaming gender in political participation in Kampung Tok Meng, Terengganu Darul Iman State, Malaysia, and to increase public knowledge and understanding about women's participation in politics. The method for implementing this service uses counseling, which includes planning, implementation, and monitoring with partners from Universiti Sultan Zainal Abidin. The evaluation instrument for this activity is a questionnaire, which is then analyzed descriptively. The results of this service show that public knowledge and understanding of women's participation in politics has finally increased. Through this activity, we can improve the awareness, motivation, and ability of women in Kampung Tok Meng to participate more actively in politics, and of course, in the end, they can apply the theory of planned behavior in gender mainstreaming to women's political participation in Kampung Tok Meng, Terengganu, Malaysia.